Language teaching research
Language Teaching Research is a peer-reviewed journal that publishes research within the area of second or foreign language teaching. Although articles are written in English, the journal welcomes studies dealing with the teaching of languages other than English as well. The journal is a venue for studies that demonstrate sound research methods and which report findings that have clear pedagogical implications.